Deuterium z-pinch as a powerful source of multi-MeV ions and neutrons for advanced applications; Physics of Plasmas; Vol. 23, iss. 3 - Klir D.; Shishlov A. V. Aleksandr Viktorovich; Kubes P.; Labetsky A. Yu.; Rezac K.; Cherdizov R. K. Rustam Koshalievich; Cikhardt J. Jakub; Cikhardtova B.; Dudkin G. N. Gennadiy Nikolaevich; Fursov F. I. Fedor Ivanovich; Garapatski A. A. Alexander Alexandrovich; Kovalchuk B. M. Boris Mikhailovich; et al. (2016, 2016)
Title screen